Instructional Design of Civic Education Based on Current Issues in the Field of National Resilience According to the Characteristics of Students at SMKN 2 Lamongan - Machsunah, Yayuk Chayatun; Ardiansyah, Verdy; Astutik, Nur Fithria Wiji (Academia Publication, 2024)
The aim of this study was to develop an instructional design for the subject of Civic Education based on current issues in the field of national resilience, tailored to the characteristics of students at SMKN 2 Lamongan. This study utilized the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The outcome of this development is the lesson planning for PKn, focusing on one of the basic competencies. From this study, it can be concluded that lesson plans oriented around current issues, aligned with student characteristics, can serve as a foundation for teachers to design innovative lessons, fostering active student participation.